CGIAR System-Level Outcomes, their Impact Pathways and Inter-Linkages - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2013)
This paper responds to a request to the ISPC from the CGIAR Fund Council and Consortium to identify the major routes through which agricultural research can address the four high-level goals, called System-Level Outcomes (SLOs), of the CGIAR and the potential linkages between research and impact pathways.